The Effect of Body Mass Index on the KYN/TRP Pathway in the Pathogenesis of Periodontitis - Zeliha Güney; Sema Merve Altıngöz (Ankara University, 2023)
ABSTRACT Purpose: The tryptophan-kynurenine (TRP-KYN) pathway is associated with inflammation and kynurenine pathway (KP) dysregulation is present in overweight and obesity. Meanwhile, obesity and periodontitis are two of the most frequent noncommunicable illnesses, and epidemiological studies show that obesity has a role in the initiation and progression of periodontitis. However, the association between elevated body mass index and KP on periodontal disease etiology is unknown. As a result, our study is aimed to investigate the possible relationship within TRP/KYN ratio and BMI relationship in periodontitis. Materials Method: The study comprised 20 periodontitis patients (P, Generalized Stage III Grade B, n=20) and 20 healthy persons (C, n=20). Clinical parameters (Bleeding index on probing (BOP), clinical attachment loss (CAL) and pocket depth (PD)), and BMI were recorded at the beginning of the study. Salivary and serum KYN/TRP ratios were analyzed by using mass spectrometry-liquid chromatography (LC-MS/MS). Results: Clinical periodontal parameters were statistically significantly higher in P group than in C group (p